Probiotic Therapy as an Adjuvant in the Treatment of Periodontal Disease: An Innovative Approach - Liliana Sachelarie; Ioana Scrobota; Ioana Romanul; Raluca Iurcov; Georgiana Ioana Potra Cicalau; Liana Todor (Medicina)
Background and Objectives: Periodontal inflammation, often linked to oral microbiota dysbiosis dominated by pathogenic bacteria, remains a significant challenge in periodontitis management. Traditional periodontal therapies primarily reduce the bacterial load but fail to restore the microbiota balance. Probiotics offer a promising therapeutic adjunct with their ability to enhance beneficial bacteria. This study investigates the effects of probiotics on the oral microbiota, inflammatory markers (IL-1β, TNF-α), and clinical parameters (gingival index, bleeding index, and periodontal pocket depth). Materials and Methods: In this pilot study, 80 patients with moderate-to-severe periodontitis were assigned to two groups. Group A received standard periodontal therapy (non-surgical periodontal therapy (NSPT)) with probiotic supplementation (Lactobacillus reuteri, 2 × 10⁹ CFU daily for 8 weeks), and Group B received standard treatment with a placebo. Microbiological changes were assessed via quantitative PCR, while inflammatory markers (IL-1β, TNF-α) were analyzed using ELISA. Clinical parameters, including the gingival index (GI), bleeding index (BI), and periodontal pocket depth (PPD), were measured at baseline (T0), 4 weeks (T1), and 8 weeks (T2) using standardized methods. Results: Probiotic therapy (Group A) significantly reduced the pathogenic bacteria and increased the beneficial bacteria levels compared to the placebo (p < 0.01). Inflammatory markers decreased by 37% (IL-1β) and 42% (TNF-α), while clinical parameters improved, with reductions in the gingival and bleeding indices (−1.5, −1.3) and a 2 mm decrease in the periodontal pocket depth (p < 0.01). Conclusions: Probiotics, as an adjunct to periodontal therapy, effectively restore the microbiota balance, reduce inflammation, and improve clinical outcomes in periodontitis.